Sexualidade, saúde e enfermidade nas obras médicas do Pedro Hispano (séc.XIII) - SERAPHIN, Catarina Stacciarini (2012)
This research intends to analyze sexuality inserted in the medical discourse of the thirteenth century, by the analysis of two important medical works assigned to the Portuguese physician Peter of Spain (1210 1277): the recipe book Thesaurus pauperum, written probably in the second half of the thirteenth century when the physician composed the papal curia and the Questiones super Viaticum, a medical commentary on the Viaticum of Ibn al Jazzār, translated and adapted by Constantine the African composed possibly in the period in which he taught in the Medical School of the University of Siena (1245-1250). During this period, sexuality permeated different fields of knowledge, integrating not only the medical discourse, but also the religious one, a discourse that had greater visibility. Thus, there was a duality concerning sexuality and its practices, that were on one hand repressed and controlled by a normative religious literature, and on the other hand were valued as important components in maintaining the health by the medical literature. This medical works still presented a discussion concerning the diseases related to sexuality, in other words, those that affect in some way the sexual practices or that present them as treatment. By the analysis of this works is possible to notice that the medical discourse diverges to some extent from the religious one, presenting a wider debate in relation to the theme, reiterating the relation among health and sexuality.